2018
DOI: 10.2298/ijgi180610007m
|View full text |Cite
|
Sign up to set email alerts
|

Application of the water quality index in the Timok River basin (Serbia)

Abstract: The paper presents an analysis of water pollution carried out on the basis of the combined physico-chemical Serbian Water Quality Index (WQI) in the Timok River basin. The analysis covers various parameters (oxygen saturation, Five-Day Biochemical Oxygen Demand or BOD 5 , ammonium ion concentration, pH value, Water Total Nitrogen or WTN, Total Suspended Solids or TSS, orthophosphate concentration, electrical conductivity, temperature and the fecal coliform bacteria parameter) the values of which were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Certain WQI scales are the result of changed water quality due tothe wastewater from human activities, industrial establishments, agricultural resources and illegal waste disposal in the basin. The computed average WQI values for the Timok River during the period of 1990-2014 showed significant oscillations in water quality and indicated high level of water pollution with organic and inorganic substances [35]. This study highlighted based on the WQI and PI that the water quality of the Auranga estuary was poor in the winter and summer seasons due to more component contamination and good water quality in the monsoon season due to more freshwater influence because of the heavy rain.…”
Section: Resultsmentioning
confidence: 76%
“…Certain WQI scales are the result of changed water quality due tothe wastewater from human activities, industrial establishments, agricultural resources and illegal waste disposal in the basin. The computed average WQI values for the Timok River during the period of 1990-2014 showed significant oscillations in water quality and indicated high level of water pollution with organic and inorganic substances [35]. This study highlighted based on the WQI and PI that the water quality of the Auranga estuary was poor in the winter and summer seasons due to more component contamination and good water quality in the monsoon season due to more freshwater influence because of the heavy rain.…”
Section: Resultsmentioning
confidence: 76%
“…Therefore, each has an assigned weight factor and an estimate of the number of points contributing to the water quality threat. By adding the products qi and wi, we come to the value of index 100 as the ideal sum of the values of all parameters (Summary of Oregon Water Quality Index Report, 1996Report, -2005Khan et al, 2005;Lumb et al, 2006;Veljković et al, 2008;Milijašević Joksimović et al, 2018;Babić et al, 2019).…”
Section: Methodology and Datamentioning
confidence: 99%
“…Several studies have been conducted on the quality of polluted river water (Milijasevic et al ., 2011; Ishiyama et al ., 2012; Atanackovic et al ., 2013; Gardic et al ., 2015; Serbula et al ., 2016; Dordievski et al ., 2018; Milijasevic Joksimovic et al ., 2018). Ishiyama et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on the quality of polluted river water (Milijasevic et al, 2011;Ishiyama et al, 2012;Atanackovic et al, 2013;Gardic et al, 2015;Serbula et al, 2016;Dordievski et al, 2018;Milijasevic Joksimovic et al, 2018). Ishiyama et al (2012) showed that the environmental impact on the water of the Danube River is small based on the chemical composition of filtered river water in the Bor mining area.…”
Section: Introductionmentioning
confidence: 99%